Age Effects in First Language Attrition: Speech Perception by Korean‐English Bilinguals. Issue 3 (20th July 2017) - Ahn, Sunyoung; Chang, Charles B.; DeKeyser, Robert; Lee‐Ellis, Sunyoung
Abstract: This study investigated how bilinguals' perception of their first language (L1) differs according to age of reduced contact with L1 after immersion in a second language (L2). Twenty‐one L1 Korean‐L2 English bilinguals in the United States, ranging in age of reduced contact from 3 to 15 years, and 17 control participants in Korea were tested perceptually on three L1 contrasts differing in similarity to L2 contrasts. Compared to control participants, bilinguals were less accurate on L1‐specific contrasts, and their accuracy was significantly correlated with age of reduced contact, an effect most pronounced for the contrast most dissimilar to L2. These findings suggest that the earlier bilinguals are extensively exposed to L2, the less likely they are to perceive L1 sounds accurately. However, this relationship is modulated by crosslinguistic similarity, and a turning point in L2 acquisition and L1 attrition of phonology appears to occur at around age 12. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the Open Science Framework athttps://osf.io/B2478 and athttps://osf.io/G4C7Z . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .